Modeled, multistage convection cooking of beef semitendinosus roasts to denature collagen and to optimize tenderness - Powell, T.H.; Hunt, Melvin C.; Dikeman, Michael E. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
In order to predict and establish cooking times and temperatures of beef to optimize tenderness and cooked yield, a computer model was developed utilizing heat and mass transfer theories. We cooked beef semitendinosus (eye of round) roasts in a forced-air convection oven using conventional or modeled, multistaged cooking. Conventional cooking was defined as cooking at 325EF to a core endpoint of 150EF. The model method was developed using a computer algorithm that predicted heat and moisture (mass) transfer during a three-stage cooking process that included preheating, holding, and finishing. The model was accurate in predicting actual cooking times and temperatures during cooking; temperature profile curves tracked closely between predicted and observed values. Roasts cooked by the modeled cooking regimen had lower Warner-Bratzler shear values than those cooked by conventional convection cooking. Collagen total unaltered fraction was lower (P<.05; 44 vs. 55%) and enzyme labile fraction was higher (56 vs. 45%, P<.05) in model cooked than in conventionally cooked samples. Cooking yield was not different for the modeled and conventional procedures. These results show that the modeled multi-stage cooking method was superior to the conventional cooking method.
Keywords: Beef; Tenderness; Modeling; Cooking; Semitendinosus; Collagen